Probing Two-way Moderation Effects: A Review of Software to Easily Plot Johnson-Neyman Figures. Issue 3 (3rd May 2020) - Lin, Hua
ABSTRACT: This review explores the possibility of generating Johnson-Neyman's interaction plot merely using the functions from software or packages without involving complex calculations. Three different programs were compared: Mplus version 8.3, the Johnson-Neyman () function in the interaction package for R version 3.6.2, and PROCESS Macro version 3.4 for IBM SPSS Statistics version 25. These three functions/software are capable of probing or providing sufficient information to probe the J-N interaction figure simply. Mplus and the Johnson-Neyman() are straightforward, including the graphing function, although the figure created in Mplus does not show the region(s) of significance. Johnson-Neyman() and PROCESS Macro provide more information in the output related to the J-N technique, reporting the region(s) of significance and the observed range of the moderator for identifying the actual region of significance. Johnson-Neyman() is superior for using the J-N technique to probe two-way moderation effects compared tootheravailable functions/software.